Commitment of adipose-resident c-kit+ progenitors to brown adipocytes contributes to adipose tissue homeostasis and remodeling - Qishan Chen; Ya Yu; Run Zhang; Qiaohang Zhao; Danqing Yu; Chun Feng; Jiaojiao Zhou; Meng Luo; Mei Yang; ShaSha Sun; Li Zhang; Min Jin (Nature Communications)
Abstract The global incidence of obesity-related metabolic disorders and their comorbidities continue to increase along with a demand for innovative therapeutic interventions. An in-depth understanding of de novo thermogenic adipogenesis is vital to harness the potential of these adipocytes. Here, we combine genetic lineage tracing and single-nucleus RNA sequencing to demonstrate that adult adipose-resident c-kit+ cells are previously unidentified brown adipocyte progenitor cells (APCs). c-kit+ APCs differentiate into brown adipocytes but not white adipocytes in adipose tissue homeostasis as well as in cold exposure-, high-fat diet (HFD)- and aging-induced adipose remodeling. More importantly, the vital role of c-kit+ APCs in the generation of brown adipocytes is indicated by decreased brown fat, impaired thermogenic capacity, and excessive fat accumulation in c-kit mutant mice of both genders. In conclusion, the present study demonstrates that adult c-kit+ APCs give rise to brown adipocytes which are responsible for fat homeostasis and remodeling. Thus, c-kit+ progenitors may be an innovative and crucial target for obesity and metabolic diseases.